Central and Eastern European attitudes in the face of union - Guerra, Simona; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
Through the analysis of data on support for and opposition to European integration in Central and Eastern Europe, this book explores how and why support for the EU has changed in this region and the factors that have led to the fall in popularity of the EU as an institution.
Keywords: Political science; Ethnology -- Europe; Elections; Europe -- Politics and government; European Union; Russia -- Politics and government; Political sociology; Political Science and International Relations; European Union Politics; Political Sociology; Russian and Post-Soviet Politics; European Politics; European Culture; Electoral Politics